RANCANG BANGUN SISTEM SMART PARKING BERBASIS IoT DENGAN MONITORING REAL-TIME MENGGUNAKAN ESP32 DAN APLIKASI WEB - Erlan Syahputra; Muh Subhan; Yogi Perdana (LPPM UNIVERSITAS BINA INSAN, 2026)
Limited parking availability and manual parking management often cause various problems, such as inefficient land use, difficulties in finding parking spaces, and increased risks of vehicle loss due to the absence of proper access control. This condition also forces users to spend more time searching for parking, which can increase fuel consumption and carbon emissions. To address these problems, this research designs and develops an Internet of Things (IoT)-based Smart Parking system using ESP32, ultrasonic sensors, RFID, and a web application. The system was developed using the Prototype method, which consists of requirements analysis, system design, implementation, and system testing. The results show that the system is able to detect vehicle presence, manage user access, identify the use of more than one parking slot by the same user, and display real-time parking information through the web application. Based on the testing results, all system functions operate properly, with an average response time of 1.8 seconds and a reliability level of 99.44%. The developed system successfully supports parking management by making it more organized, secure, and efficient